Energy efficient task distribution with efficient deployment and scheduling of sensor nodes in WSN. (2017) - Singh, Devesh Pratap; Pant, Bhasker
Lifetime of the network plays a vital role in working wireless sensor networks. Network lifetime can be improved by the efficient use of present sensor nodes in wireless sensor nodes. In this paper, our objective is to deploy and schedule the sensor nodes in such a manner that improves the lifetime and provides a way to distribute the tasks among the sensor nodes that completes the task on the basis of priority and accuracy. Thus, the overall objective of this paper is to calculate the optimised location of sensor nodes contain a fix sensing range and schedule the sensor nodes that maximises the lifetime. The upper bound of network lifetime can be pre-calculated mathematically, we are applying this knowledge to find the locations of sensor nodes that improves the lifetime. Further, the nodes are scheduled and task is distributed among the sensor nodes that achieve this upper bound. In this paper, we are applying teaching learning algorithm to find the deployment location and schedule followed by an algorithm for task distribution. The comparative study shows that our method outperforms as compared to naïve methods.